Community Activity in Environmental Management Mangrove Forest in Pariaman City - Arif Setiawan; Abdul Razak; Nurhasan Syah; Skunda Diliarosta (Postgraduate School, Universitas Negeri Padang, 2023)
The potential and unique natural resources in the Pariaman Mangrove Forest have a very significant role in the economic, social, cultural, and environmental development of coastal communities. Environmental management of the Pariaman Mangrove Forest is one of the efforts to support the development of coastal areas optimally, wisely, and responsibly, of course by involving community participation and various related parties and while still paying attention to the environmental carrying capacity of the Pariaman Mangrove Forest. This research aims to provide an overview of community activity in managing the Mangrove Forest environment in Pariaman City. Enthusiasm, desires, and hopes as well as the social concern of the local community are forms of community participation in efforts to manage the Mangrove Forest environment. Community participation is a supporting factor in efforts to develop the coastal area of Pariaman City. The description of community participation in the environmental management of Mangrove Forests is shown by the high level of community desire to protect and preserve them as well as their hope for efforts to protect or improve Mangrove Forests. The form of community participation is voluntary or self-directed participation.